Consumption of plus-size clothing: a systematic review - Paula, Guilherme Rodrigues; Ferreira, Frederico Leocádio; Christino, Juliana Maria Magalhães (Revista de Administração da UFSM, 2023)
Purpose: The consumption of plus-size clothing is part of a growing market, but it is always surrounded by cloudy issues, such as the lack of a precise direction when it comes to producing and selling these garments and the prejudice surrounding the various areas of the fat body. Employing a systematic review, this paper aims to understand the consumption of plus-size clothing through an in-depth analysis of studies published in various areas on the subject. Design/Methodology/Approach: A systematic review was conducted in the WEB OF SCIENCE and SCOPUS databases, and 35 pertinent articles published up to the year 2020 were identified, read and analyzed in detail in this paper. Findings: The articles originated three thematic categories: Plus-size Consumption, which deals with consumer experience with the industry; Plus-size in the Media, which addresses aspects of advertising and plus-size models; Plus-size Identity, which covers identity formation and social influences. Research Limitations/Implications: Fourteen theoretical gaps were pointed out to be worked on by future studies, comprising online retailing, identity, demographic, contextual, methodological, cultural, and social issues. Originality/value: The present study represents pioneering work in the field of research on plus-size clothing, and, to the best of our knowledge, it is the first of its kind to conduct a comprehensive and systematic analysis of studies published in various areas related to this topic. While the plus-size apparel and retail market remain shrouded in nebulous issues, this research stands out as a valuable contribution by providing profound insights into consumption in this segment. Moreover, by identifying theoretical gaps and offering suggestions for future research, the study promotes advancements in knowledge and understanding of this emerging area. Its academic significance and potential impact on the industry make it crucial to developing more informed and inclusive strategies for the plus-size fashion sector.